Pengaruh Pemahaman Peraturan Perpajakan dan Kualitas Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak dengan Sosialisasi Perpajakan Sebagai Pemoderasi (Studi Kasus Wajib Pajak UMKM di KPP Pratama Pekanbaru Tampan) - Widya Febriyanti; Dwi Fionasari; Agustiawan Agustiawan; Rama Gita Suci (Politeknik Negeri Bengkalis, 2023)
This study aims to examine whether there is an influence between the understanding of regulations and the quality of tax service services on taxpayer compliance with taxation taxes as moderating. The data used in this study are primary data. This type of research is quantitative. The object of this research is MSME taxpayers who are registered at the Tampan KPP Pratama Pekanbaru City. The sample collection method used random sampling method. Samples were taken as many as 100 MSME taxpayers. The data analysis test uses the Moderated Regression Analysis (MRA) method which is processed using SPSS 24. The results of this study indicate that the understanding of tax regulations and the quality of tax services have an effect on taxpayer compliance. Furthermore, the socialization of taxation is able to moderate the effect of understanding regulations and the quality of tax service services on taxpayer compliance.Keywords: Understanding of Tax Regulations, Quality of Fiscus Service, Socialization of Taxpayer Compliance